Surgical treatment of pulmonary atresia with ventricular septal defect at Hue central hospital - Hung, Nguyen Xuan; Dung, Nguyen Duc; An, Tran Hoai; Vinh, Bui Duc An; Thanh, Nguyen Thi Dieu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.